The intervention effects of Lactobacillus casei LC2W on Escherichia coli O157:H7 -induced mouse colitis - Guangqiang Wang; Hongyu Tang; Ying Zhang; Xiang Xiao; Yongjun Xia; Lianzhong Ai (Food Science and Human Wellness)
This study investigated the intervention effects of Lactobacillus casei LC2W in murine (SPF C57BL/c) challenge infection models induced by Escherichia coli O157: H7. Mice were fed streptomycin with water for 3 days prior to intragastric gavage by E. coli O157:H7 (Control) or L. casei LC2W together with E. coli O157:H7 (Intervention) to explore the role of L. casei LC2W by biochemical indicators, histological evaluation, expression of colonic pro-inflammatory and intestinal barrier factors related to enteritis. Results showed that the administration of L. casei LC2W was able to alleviate the symptoms of colitis induced by E. coli O157:H7, exhibiting lower weight loss as well as more intact colon tissue. Furthermore, L. casei LC2W could down-regulate the expression of pro-inflammatory cytokines (TNF-α, IL-6, and IL-1β) and protect the intestinal barrier function by improving the level of MUC2, ZO-1 and E-cadherin 1 compared to the control group. These results demonstrate that L. casei LC2W can reduce the severity of E. coli O157:H7 infection, and suggest L.casei LC2W may maintain the immune balance and intestinal barrier to reduce colitis. In addition, we found the effect of intervention is similar to that of prevention, which is better than that of treatment.